Golf skill: The effective acquisition and application of biomechanics - Lumsden, R. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Q Golf primarily works with elite development players and tour players, within which there are an increasing number of injuries occurring. Case study examples will be provided for: Technology used to capture swing mechanics and measure club delivery and ball flight information; Data from 3D analysis and ball flight measures and the relationships between these parameters; How this information is utilized and interpreted to establish technical priorities; Practical application of this information and how it is communicated to players and their coaches; Use of biofeedback training to help players establish what their focus needs to be during the swing and accelerate skill learning; Victorian Institute of Sport player - Improvements in swing dynamics.